Insights into the Fungicide Prothioconazole and Its Metabolite in Wheat: Residue Behavior and Risk Assessment - Qingkui Fang; Zixuan Yan; Chengzhi Zhang; Yanhong Shi; Zhaoxian Zhang; Quan Gao; Jinjing Xiao; Min Liao; Chuanyong Qi; Haiqun Cao (Agronomy, 2023)
To clarify the residue formation of prothioconazole and its main metabolite in wheat plants, the uptake, translocation, and metabolism of prothioconazole in wheat roots and leaves were investigated by nutrient solution culture and the spraying method. The results showed that prothioconazole and its metabolites showed a trend of increasing and then decreasing in wheat plants under two treatment methods, and the concentration of prothioconazole and its metabolites was higher in the high-concentration group (5000 μg/mL) than in the low-concentration group (1000 μg/mL). The transferability from stem to leaf was stronger than that from root to stem. In the nutrient solution culture, prothioconazole and its metabolites were mainly enriched in wheat roots. The concentration of prothioconazole in wheat roots increases with the increase in prothioconazole concentration and was significantly higher than the prothioconazole concentration on stems and leaves. In wheat leaves in the spraying method, prothioconazole and its metabolites were conducted from leaves to stems and roots up to the nutrient solution. Prothioconazole-desthio was detectable in wheat nutrient solution, while prothioconazole was not detected. Analysis of actual samples of 9 wheat grains and 28 flours showed that the residues of prothioconazole and its metabolites met the maximum residue limit (0.1 mg/mL) set in China and by the Codex Alimentarius Commission. The results will provide a theoretical basis for the scientific use of prothioconazole and food security assurance.